Coronary bypass in left ventricular dysfunction and differential cardiac recovery. (November 2017) - Lozonschi, Lucian; Kohmoto, Takushi; Osaki, Satoru; De Oliveira, Nilto C; Dhingra, Ravi; Akhter, Shahab A; Tang, Paul C
Background: We aimed to examine the efficacy of surgical revascularization with respect to improvement in ventricular function and survival in patients with ischemic cardiomyopathy and poor left ventricular function. Methods: We retrospectively analyzed the data of 429 patients (median age 64.6 years, 81.1% male) with ejection fractions <40% undergoing isolated primary coronary artery bypass grafting from 2000 to 2016. Techniques included on-pump cardioplegic arrest ( n = 312), off-pump ( n = 75), and on-pump beating heart ( n = 42). Propensity matching was performed to compare the cardioplegic arrest group ( n = 114) with the combined off-pump and beating heart groups ( n = 114). Results: Postoperatively, ejection fraction increased by 10.1% ± 13.1% (from 31.4% ± 7.1% to 41.6% ± 13.6%; p < 0.001) and mitral regurgitation grade improved ( p < 0.001) but right ventricular function on echocardiographic assessment worsened over time ( p = 0.04). No difference in ejection fraction improvement was seen in the time periods <1 (9.8% ± 11.2%), 1–5 (11.6% ± 14.5%), and >5 (8.8% ± 14.2%) years ( p = 0.442). Following propensity matching, there was no significant difference between the combined off-pump/beating heart and cardioplegic arrest groups with respect to survival or postoperative complications. Conclusions: Patients with moderate to severe left ventricular dysfunction experience long-term improvement in left ventricular ejection fraction after coronary artery bypass. However, right ventricular function often continues to decline, contributing to persistent or worsening heart failure symptoms and late mortality. No difference in survival was seen between the 2 techniques.